Adaptive Mechanisms of Somatostatin-Positive Interneurons after Traumatic Brain Injury through a Switch of α Subunits in L-Type Voltage-Gated Calcium Channels. (19th August 2021) - Ihbe, Natascha; Le Prieult, Florie; Wang, Qi; Distler, Ute; Sielaff, Malte; Tenzer, Stefan; Thal, Serge C; Mittmann, Thomas
Abstract: Unilateral traumatic brain injury (TBI) causes cortical dysfunctions spreading to the primarily undamaged hemisphere. This phenomenon, called transhemispheric diaschisis, is mediated by an imbalance of glutamatergic versus GABAergic neurotransmission. This study investigated the role of GABAergic, somatostatin-positive (SST) interneurons in the contralateral hemisphere 72 h after unilateral TBI. The brain injury was induced to the primary motor/somatosensory cortex of glutamate decarboxylase 67–green fluorescent protein (GAD67-GFP) knock-in mice at postnatal days 19–21 under anesthesia in vivo. Single GFP+ interneurons of the undamaged, contralateral cortex were isolated by fluorescence-activated cell sorting and analyzed by mass spectrometry. TBI caused a switch of 2 α subunits of pore-forming L-type voltage-gated calcium channels (VGCC) in GABAergic interneurons, an increased expression of CaV1.3, and simultaneous ablation of CaV1.2. This switch was associated with 1) increased excitability of single SST interneurons in patch-clamp recordings and (2) a recovery from early network hyperactivity in the contralateral hemisphere in microelectrode array recordings of acute slices. The electrophysiological changes were sensitive to pharmacological blockade of CaV1.3 (isradipine, 100 nM). These data identify a switch of 2 α subunits of VGCCs in SST interneurons early after TBI as a mechanism to counterbalance post-traumatic hyperexcitability.